Efficacy and feasibility of a digital speech therapy for post-stroke dysarthria: protocol for a randomized controlled trial - Kim, Yuyoung; Kim, Minjung; Kim, Jinwoo; Song, Tae-Jin (Frontiers in Neurology, 2024)
Background Dysarthria is a motor speech disorder caused by various neurological diseases, particularly stroke. Individuals with post-stroke dysarthria experience impaired speech intelligibility, communication difficulties, and a reduced quality of life. However, studies on the treatment of post-stroke dysarthria are lacking. Digital speech therapy applications have the advantages of being personalized and easily accessible. However, evidence for their efficacy is not rigorous. Moreover, no studies have investigated both the acute to subacute, and chronic phases of stroke. This study aims to investigate the efficacy and feasibility of digital speech therapy applications in addressing these gaps in dysarthria treatment. Methods and design This study is a multicenter, prospective, randomized, evaluator-blinded non-inferiority trial. We aim to recruit 76 participants with post-stroke dysarthria. Eligible participants will be stratified based on the onset period of stroke into acute to subacute, and chronic phases. Participants will be randomized in a 1:1 to receive either a personalized digital speech therapy application or conventional therapy with a workbook for 60 min daily, 5 days a week, for 4 weeks. The primary outcome is the improvement in speech intelligibility. This will be measured by how accurately independent listeners can transcribe passages read by the participants. Secondary outcomes, which include speech function, will be evaluated remotely by speech-language pathologists. This includes the maximum phonation time, oral diadochokinetic rate, and percentage of consonants correct. Participants’ psychological well-being will also be assessed using self-report questionnaires, such as depressive symptoms (Patient Health Questionnaire-9) and quality of life (Quality of Life in the Dysarthric Speaker scale). The trial will also assess the feasibility, participant adherence, and usability of the application. Rigorous data collection and monitoring will be implemented to ensure patient safety. Conclusion This trial aims to investigate the efficacy and feasibility of digital speech therapy applications for treating post-stroke dysarthria. The results could establish foundational evidence for future clinical trials with larger sample sizes. Clinical trial registration Clinicaltrials.gov, identifier: NCT05865106.